Adjustment Costs of Trade Liberalization : Estimations for the Russian Labor - Akhmedov, Akhmed (World Bank, Washington, DC, 2017)
The paper investigates adjustment costs of trade liberalization in Russia by estimating various labor market elasticities with respect to indicators of trade liberalization in the 90-ies. In particular, the influence of tariff reduction on demand for labor is estimated, inter-sectoral employment flows in recent years and their determinants are studied, as well as determinants of sectoral wage premiums and of wage differentials between skilled and unskilled labor. The estimated elasticities of labor demand and wages show to be of very moderate size implying a modest adjustment cost in the labor market.